INFLUENCE OF GREEN INNOVATION ON CONSUMER PURCHASE INTENTIONS FOR ECO-FRIENDLY PRODUCTS - Budi Setiawan; Henry Sumurung; Nurul Salwa (Kesatuan Press, 2024)
This research investigates the impact of green innovation on green purchase intentions for environmentally friendly products, with environmental concerns as a mediating variable. A survey was employed to gather data from consumers familiar with eco-friendly straw products. Structural equation modeling (SEM) via AMOS software was utilized for data analysis. Primary data was collected through questionnaires distributed to consumers knowledgeable about environmentally friendly straw products. Purposive sampling was employed, resulting in a sample size of 385 respondents. Findings indicate a significant positive relationship between green innovation and environmental concerns. Furthermore, environmental concerns positively influence green purchase intentions, suggesting that higher environmental concerns correlate with a greater likelihood of purchasing environmentally friendly products. However, no significant influence of green innovation on purchase intentions was observed. Future research should investigate the relationship between green innovation, environmental concerns, and purchase intentions. The insights gained from this study can offer valuable recommendations for individuals interested in using environmentally friendly products, enabling them to enhance their green purchase intentions effectively.